2011
DOI: 10.3109/0886022x.2011.623499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mirtazapine on Oxidative Stress Created in Rat Kidneys by Ischemia-Reperfusion

Abstract: In this study, the effect of mirtazapine on rat kidneys versus ischemia-reperfusion (IR) damage was biochemically and histopathologically investigated. The results have shown that malondialdehyde (MDA) level of healthy rat group is 15.2 mol/g protein. The level of this substance was measured as 26.7 mol/g in only ischemia group. The MDA levels of IR and mirtazapine + renal ischemia-reperfusion (MRIR) groups were 39 ± 17.6 mol/g protein. While myeloperoxidase activity of healthy rat group was 20.2 u/g, the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 30 publications
1
29
0
1
Order By: Relevance
“…However, more directly related to our findings are two recent studies demonstrating that Mirtazapine treatment protects kidneys from oxidative damage caused by ischemia–reperfusion injury and neurons from oxidative damage caused by cisplatin, in rats (Tok et al ., 2012; Gulec et al ., 2013). …”
Section: Discussionmentioning
confidence: 99%
“…However, more directly related to our findings are two recent studies demonstrating that Mirtazapine treatment protects kidneys from oxidative damage caused by ischemia–reperfusion injury and neurons from oxidative damage caused by cisplatin, in rats (Tok et al ., 2012; Gulec et al ., 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The damage caused by ischemiareperfusion in many organs, such as the brain, heart, lungs, liver and intestines, has been investigated, and free radicals were found to be one of the major components of ischemiareperfusion damage [17][18][19][20][21][22]. Tok et al [23] reported that the levels of oxidant indicators such as MDA and MPO increased, whereas the levels of antioxidant indicators such as GSH and GST decreased. Yiğiter et al [24] reported an increase in the MDA level and a decrease in the GSH level in kidney tissues with damage related to ureter ligation.…”
mentioning
confidence: 99%
“…There are studies demonstrating that the amount of MDA in the renal I/R damage gets significantly high compared to a healthy tissue. 3 Also in MPO activity in the renal tissue of the RIR group, a significant increase in comparison to the sham group was determined. MPO secreted from the PMNL leads to the production of ROS, such as O À 2 , H 2 O 2 , and OH and transforms H 2 O 2 into hypochlorous acid radical (HOCl), which is a powerful oxidant, in the presence of Cl ion.…”
Section: Discussionmentioning
confidence: 99%
“…The period of time the animals remained inactive in a supine position is regarded as an appropriate time span for the surgical attempt. 3 Within this period of time, the unilateral left kidneys of all the rats were reached through the incision on their dorsal sections. Afterwards, except for the SG, 1-h-ischemia was generated by attaching clips to the renal artery and the veins reaching the kidney.…”
Section: Surgical and Pharmacological Proceduresmentioning
confidence: 99%
See 1 more Smart Citation